Development knowledge and experience: from Bangladesh to Afghanistan and beyond - Chowdhury A Mushtaque R; Aminul Alam M; Ahmed Jalaluddin (The World Health Organization, 2006)
PROBLEM: In Afghanistan the challenges of development are daunting, mainly as a result of many years of conflict. The formation of a new government in 2001 paved the way for new initiatives from within and outside the country. BRAC (formerly Bangladesh Rural Advancement Committee), a Bangladeshi nongovernmental organization with a long history of successful work, extended its development model to Afghanistan in 2002. LOCAL SETTING: Provincial Afghanistan. APPROACH: BRAC has implemented programmes in Afghanistan in the areas of health, education, microfinance, women's empowerment, agriculture, capacity development and local government strengthening, and has taken many of these programmes to scale. RELEVANT CHANGES: With a total staff of over 3000 (94% Afghan and the rest Bangladeshis), BRAC now works in 21 of the country's 34 provinces. BRAC runs 629 non-formal primary schools with 18 155 students, mostly girls. In health, BRAC has trained 3589 community workers who work at the village level in preventive and curative care. BRAC runs the largest microfinance programme in the country with 97 130 borrowers who cumulatively borrowed over US$ 28 million with a repayment rate of 98%. LESSONS LEARNED: Initial research indicates significant improvement in access to health care. Over three years, much has been achieved and learned. This paper summarizes these experiences and concludes that collaboration between developing countries can work, with fine-tuning to suit local contexts and traditions.